The Effects of Regional Governance, Education, and In‐Migration on Business Performance. (12th December 2019) - Nguyen, Bach; Canh, Nguyen Phuc
SUMMARY: National institutional settings are important to small business performance. However, national institutions take time to change. So, is there any way to boost firm performance in 'weak' institutional environments? This study aims to answer this question by examining the role of local institutions represented by the quality of local governance, instead of the very broad national constitutional configurations. Moreover, it is suggested that regional human capital, whether locally built‐up (through local education) or externally imported (through in‐migrants) is able to strengthen the positive impacts of local governance on small business performance. A test on more than 1.3 million firm‐year observations of Vietnamese small businesses confirms the moderating effects of education and in‐migration on the relationship between local governance and firm performance.